2020
DOI: 10.1093/mnras/staa3534
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the multiphase circumgalactic medium shared between a dwarf and a massive star-forming galaxy at z∼0.4

Abstract: The multi-phase circumgalactic medium (CGM) arises within the complex environment around a galaxy, or collection of galaxies, and possibly originates from a wide range of physical mechanisms. In this paper, we attempt to disentangle the origins of these multi-phase structures and present a detailed analysis of the quasar field Q0122−003 field using Keck/KCWI galaxy observations and HST/COS spectra probing the CGM. Our re-analysis of this field shows that there are two galaxies associated with the absorption. W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 110 publications
0
7
0
Order By: Relevance
“…Several recent works have demonstrated that many absorbers likely arise from complex galaxy structures and galaxy groups, not simply single galaxies evolving in isolation (Péroux et al 2019;Hamanowicz et al 2020;Chen et al 2020;Narayanan et al 2021). The high incidence of CGM gas within the virial halos of isolated dwarf galaxies (Johnson et al 2017), coupled with the recent identification of a dwarf galaxy at small projected separation from an absorber initially thought to be associated with a massive galaxy over 300 kpc away (Muzahid et al 2015;Nateghi et al 2021), highlights the need for deep galaxy spectroscopy to fully characterize the galactic environment, critical to understanding the true nature of CGM absorbers.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent works have demonstrated that many absorbers likely arise from complex galaxy structures and galaxy groups, not simply single galaxies evolving in isolation (Péroux et al 2019;Hamanowicz et al 2020;Chen et al 2020;Narayanan et al 2021). The high incidence of CGM gas within the virial halos of isolated dwarf galaxies (Johnson et al 2017), coupled with the recent identification of a dwarf galaxy at small projected separation from an absorber initially thought to be associated with a massive galaxy over 300 kpc away (Muzahid et al 2015;Nateghi et al 2021), highlights the need for deep galaxy spectroscopy to fully characterize the galactic environment, critical to understanding the true nature of CGM absorbers.…”
Section: Introductionmentioning
confidence: 99%
“…However note that, as long as a part of cloud assumed to have uniform density and metallicity irradiated with a UV background, uncertainties arising from UV background will be similar to the one presented here. For example, even for multi-phase gas as invoked in many studies (e.g, Pachat et al 2016Pachat et al , 2017Nateghi et al 2021;Haislmaier et al 2020), each phase will have similar uncertainty from UV background. Even with innovative techniques to models individual cloudlets as presented in Sameer et al (2021), each cloudlet and its phase will suffer with same uncertainty from UV background as long as a preferred UV background model is fixed for the inference.…”
Section: Other Uncertainties and Caveatsmentioning
confidence: 99%
“…This term is related to the location above the mid-plane where the lagging halo velocity component begins to matter and 𝑣 los becomes dominated by an exponentially declining term. Following previous studies (e.g., Steidel et al 2002;Kacprzak et al 2010aKacprzak et al ,b, 2011bKacprzak et al , 2019French & Wakker 2020;Nateghi et al 2021) we are forcing the disc to be a thick, nearly-rigid rotator, where material far above the disc plane is rotating along with the disc. This places our low-and high-ionization clouds high above the galactic disc at a high angle.…”
Section: Physical Geometry and Originmentioning
confidence: 99%